In silico study of four new phenoxybenzoic acid - isatin derivatives: targeting VEGFR and cancer - Kamalaldeen, Faidh Yahya; Alibeg, Ammar Abdul Aziz (Pharmakeftiki, 2025)
Cancer remains a major global health challenge, necessitating the development of novel therapeutic agents. This study hypothesizes that phenoxybenzoic acid derivatives can effectively inhibit the vascular endothelial growth factor receptor (VEGFR; Protein Data Bank code: 4ASE); a key molecular target in cancer therapy. Four compounds – designated F1, F2, F3, and F4 – were designed and synthesized to test this hypothesis. Their molecular structures were sketched using ChemDraw Ultra version 12.0, and their binding affinities were evaluated through molecular docking simulations conducted with the Molecular Operating Environment (MOE) program. Docking scores and root-mean-square deviation values were analysed in order to assess the compounds’ potential effectiveness. Compared to sorafenib, a clinically approved VEGFR inhibitor, the synthesized compounds exhibited significant binding affinities within the receptor’s active site, supporting their potential as anticancer agents. These findings provide a rationale for further biological evaluation and optimization of these compounds for targeted cancer therapy.